Perinatal Outcome in Term Pregnancies with Isolated Oligohydramnios (Medical Forum Monthly, 2020)
Objective: To compare the perinatal outcome in pregnancies with isolated oligohydramnios induced at 37 weeks to those with isolated oligohydramnios observed till 40 weeks.Study Design: Randomized Control Trial (RCT) study.Place and Duration of Study: This study was conducted at the Gynae/Obs Unit II, Holy Family Hospital, Rawalpindi from February 2015 to July 2015.Materials and Methods: A total of 144 patients were enrolled (72 patients in each group). GROUP A included pregnant ladies with oligohydramnios for whom induction of labour was done. GROUP B included pregnant ladies with oligohydramnios for whom expectant management was done.Results: Meconium staining of liquor was positive in 23.61 % of group A and 18.05% of group B babies with a P value of 0.835. Excellent APGAR score in group A and B were seen in 83.33% and 77.77 % of babies respectively with a P value of 0.400.Conclusion: Perinatal outcome in isolated oligohydramnios induced at 37 weeks is same as with expectant management of isolated oligohydramnios at term.